К.КАРИМОВТЫҢ «АҒАБИЙ» РОМАНЫНДА РЕҢЛЕРДИ БИЛДИРИЎШИ СӨЗЛЕР ҚАТНАСЫНДА ЖАСАЛҒАН ТАРИЙХЫЙ ЖӘМИЙЕТЛИК-СИЯСИЙ ЛЕКСИКА - Зайрова, Қ. (FAN va JAMIYAT, 2019)
The article deals with the social-political lexis which is presented by words defining colour in the historical novel «Agabiy» by K.Karimovs. The analysis of the work shows that there are many historical words in the novel presented by the social-political lexics including the words denoting colour. They are used in both: direct and transferred meaning. The social-political vocabulary also includes the words connected with governing by a state, country and people.